2009
DOI: 10.2478/v10006-009-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Recursive identification algorithm for dynamic systems with output backlash and its convergence

Abstract: This paper proposes a recursive identification method for systems with output backlash that can be described by a pseudoWiener model. In this method, a novel description of the nonlinear part of the system, i.e., backlash, is developed. In this case, the nonlinear system is decomposed into a piecewise linearized model. Then, a modified recursive general identification algorithm (MRGIA) is employed to estimate the parameters of the proposed model. Furthermore, the convergence of the MRGIA for the pseudo-Wiener … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 15 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Unfortunately, there are only few contributions in the literature on the identification of systems with hard nonlinearities [1,30,34] and even fewer on backlash identification [3,12,13,29,38]. To the authors best knowledge, no contribution can be found which addresses the identification of cascade systems with time-varying input backlash.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, there are only few contributions in the literature on the identification of systems with hard nonlinearities [1,30,34] and even fewer on backlash identification [3,12,13,29,38]. To the authors best knowledge, no contribution can be found which addresses the identification of cascade systems with time-varying input backlash.…”
Section: Introductionmentioning
confidence: 98%
“…According to the physical architecture of the mentioned mechanical transmission system, we note that the backlash is embedded between two linear dynamic subsystems. Thus, this system can be described by a so-called sandwich system with backlash [1][2][3]. In practical engineering, the input and output of gearbox are considered as the internal variables, which are usually not measurable directly.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, construction of a non-smooth observer for sandwich system with backlash to estimate its states is an important and meaningful work for the optimal control and fault diagnosis research of the mechanical systems involved with backlash. For the convenience of constructing the observer, a state space model based on the model proposed in [2] is developed. In the state space model, the in linear subsystem 1 L can be described by 1 1 11 1 1 (2) and the output linear subsystem 2 L can be described by:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a special case of two-block models consisting of the cascade of linear dynamic and nonlinear dynamic blocks has to be used. For example, the cascade model structure consisting of a linear dynamic block followed by a nonlinear dynamic block was often used for the identification of nonlinear dynamic systems with output backlash [16][17][18].…”
Section: Introductionmentioning
confidence: 99%